Primary School Teacher Professionalism: Analysis Based On Principal Managerial Competencies and Teacher Tpack In Rumbai District Pekanbaru City - Mely Jumika; Erni; Erlisnawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze the influence of principals' managerial competence and teachers' Technological Pedagogical Content Knowledge (TPACK) on the professionalism of public elementary school teachers in Rumbai District, Pekanbaru City. This study uses a quantitative, ex post facto research design. The population was 360 teachers from 20 public elementary schools in Rumbai District. The research sample was determined using the Slovin formula and obtained 190 respondents with a proportional random sampling technique. The instrument trial was conducted on 30 teachers outside the research sample. The data collection technique used a distributed questionnaire. Data analysis used SPSS version 26, including descriptive and inferential statistical analyses, as well as classical assumption tests and hypothesis tests. The novelty of this study lies in testing the simultaneous influence of principals' managerial competence and teachers' TPACK on teacher professionalism at the elementary school level. The results showed that principals' managerial competence and TPACK had a positive and significant effect on teacher professionalism. In addition, principals' managerial competence and teachers' TPACK simultaneously had a positive and significant effect on teacher professionalism, contributing 42.5% in the moderate category. Research findings show that increasing teacher professionalism is influenced by the principal's ability to manage the school effectively and by teachers' ability to integrate technology, pedagogy, and content into the learning process.